Clinical and Phenotypic Correlates of Mitral Valve Prolapse in Marfan Syndrome: The Cornell Aortic Aneurysm Registry - Nupoor Narula; Yosef Schwartz; Richard B. Devereux; Xiaoyue Ma; Jonathan W. Weinsaft; Leonard Girardi; Mary J. Roman (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background Mitral valve prolapse (MVP) is highly prevalent in Marfan syndrome (MFS), but its associations with significant valvular regurgitation, the need for mitral valve (MV) surgery or elective aortic root replacement, and the occurrence of aortic dissection in MFS are not fully elucidated. Methods Imaging, anthropometric, cardiovascular disease, and surgical data were compared in patients with and without MVP in a large, single‐center MFS registry. Results Of 352 patients with MFS, MVP was present in 237 (67.3%) and was more common in women (73.3% versus 59.9%, P=0.007). Patients with MVP had distinct skeletal features, including a lower body mass index, and higher prevalences of scoliosis surgery, arachnodactyly, and skin striae. Although rates of MV surgery were similar in men (14.7%) and women (16.9%), women underwent surgery at a younger age (35.4±14.5 versus 43.0±14.6 years; P=0.04). Patients who underwent MV surgery were more likely to undergo aortic root replacement (73.2% versus 42.6%, P<0.001) and to have a type B aortic dissection (25.0% versus 11.8%, P=0.01). Conclusions MVP is highly prevalent in MFS and more likely to necessitate MV surgery compared with the general population, particularly among women. The associations of MV surgery with aortic root replacement and type B dissection indicate that MVP associated with the need for mitral surgery tracks with a more severe aortic phenotype in MFS.